Peran Majelis Ta'lim dalam Meningkatkan Keharmonisan Rumah Tangga (Studi Kasus di Asrama Lingkungan Hidup Kelurahan Semper Barat, Cilincing, Jakarta Utara) - Nakhar Faanji Ma'ruf; Muslihun M (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the role of Majelis Ta'lim in improving household harmony at the Environmental Dormitory (Asrama Lingkungan Hidup) in Semper Barat Village, Cilincing, North Jakarta. A qualitative approach with a case study method was employed. Data were gathered through in-depth interviews, participatory observation, and documentation. The findings reveal that Majelis Ta'lim plays a significant role across three main dimensions: first, enhancing the religious understanding of family members; second, strengthening communication between spouses and across generations; and third, building a solid social support network within the dormitory community. Activities such as classical text recitation (kitab kuning), parenting seminars, interactive discussions, and social service events concretely contribute to creating a more harmonious household atmosphere. Key supporting factors include community leader support, active member participation, and local government involvement. Measurable impacts include: 85% of respondents reporting better family relationships, 80% experiencing improved communication quality, and only 5% of active families experiencing divorce compared to 15% of inactive families (LSI, 2023).